A propósito de la categoría de género : leer a Joan Scott - Tarrés, María Luisa (El Colegio de México, 2013)
This article is to Joan Scott’s contribution to the contemporary feminist thought. Fromhis early work, Scott moved the question in the cause or the reason for the exclusion of women in history and everyday experience, and redirects to the how it happens. She reveals its mechanisms and develops the perspective of gender from different disciplines that continues to this day. In this sense, we rescued the ensuingdiscussion about the status of women, whose nucleus is organized from a reviewof Scott’s proposal. To do this, we rely on two existing currents of contemporaryacademic debate: the postcolonial, based on a critique to the Western feminism, andpostmodern, represented by the early work of Judith Butler, who from a position es-sentially philosophical and psychoanalytic radically questions the category of genderand its place in the construction of subjective identities.